Liferider : heart, body, soul, and life beyond the ocean - Hamilton, Laird; Borra, Julian (Rodale, 2019)
"Millions of us increasingly seek happiness in fads and self-help books, reaching upward every day toward some enlightened state that we wish to attain. Surfing icon Laird Hamilton is more intent on looking inward and appreciating the brilliant creatures we already are. In Liferider, Laird uses five key pillars-Death & Fear, Heart, Body, Soul, and Everything Is Connected-to illustrate his unique worldview and life practices, offering inspiration to anyone who wants to elevate their ordinary, landlocked lives to do extraordinary things. This is Laird Hamilton in his own words--raw, honest, and unvarnished--on topics he has rarely explored before. Based on extensive interviews and conversations between Laird and his coauthor, Julian Borra, with additional insights from Laird's wife, pro-volleyball player Gabby Reece, Liferider takes on human resilience, relationships, business, technology, risk-taking, and the importance of respecting the natural world, all through the lens of Laird's extraordinary life both in and beyond the ocean"--